Effect of counseling program on early postpartum breast feeding by nursery mother - Ahmed, Amany; M. Mohamed, Nour Elhoda; M. Mahmmed, Thorea (International Journal of Advanced Nursing Studies, 2016)
Background: Breast feeding is a learnt skill. Most primipara, if encouraged, and educated can successfully breast-feed. The aim of the present study was to assess the effect of postpartum breast feeding counseling program on the awareness of correct breast feeding.Methods: This prospective study was conducted in, Sohag University Hospital, between March to December 2015, on 93 primiparous women who were interviewed to collect data through a questionnaire formulated by the researchers, for assessment of breast feeding knowledge (pre-test evaluation) and for administration of counseling program one hour after delivery. Those women were interviewed again 3 hours post-partum to assess knowledge (post-test evaluation) and the initiation of breast feeding after counseling program.Results: The mean age of women in the present study was 24.3Â±6.9 years. The majority of women were house wives (57%), literate (84%), and intended for â‰¥2years birth spacing (77%). Counseling program to primiparous women resulted in significant higher % of correct general breast feeding knowledge, knowledge about breast fed babies and breast milk, as well as knowledge regarding special situations and problems during breast feeding.Conclusions: Counseling breast feeding program in the early postpartum period is an effective method to encourage mother for breast feeding.